Immunoglobulin G glycome composition in transition from premenopause to postmenopause - Deriš, Helena; Kifer, Domagoj; Cindrić, Ana; Petrović, Tea; Cvetko, Ana; Trbojević-Akmačić, Irena; Kolčić, Ivana; Polašek, Ozren; Newson, Louise; Spector, Tim; Menni, Cristina; Lauc, Gordan (iScience, 2022)
Gonadal hormones affect immunoglobulin G (IgG) glycosylation, and the more proinflammatory IgG glycome composition might be one of the molecular mechanisms behind the increased proinflammatory phenotype in perimenopause. Using ultra-high-performance liquid chromatography, we analyzed IgG glycome composition in 5,080 samples from 1940 pre-, peri-, and postmenopausal women. Statistically significant decrease in galactosylation and sialylation was observed in postmenopausal women. Furthermore, during the transition from pre- to postmenopausal period, the rate of increase in agalactosylated structures (0.051/yr; 95%CI = 0.043–0.059, p < 0.001) and decrease in digalactosylated (−0.043/yr; 95%CI = −0.050 to −0.037, p < 0.001) and monosialylated glycans (−0.029/yr; 95%CI = −0.034 to −0.024, p < 0.001) were significantly higher than in either pre- or postmenopausal periods. The conversion to the more proinflammatory IgG glycome and the resulting decrease in the ability of IgG to suppress low-grade chronic inflammation may be an important molecular mechanism mediating the increased health risk in perimenopause and postmenopause. [Display omitted] •Different levels of IgG N-glycans in premenopausal and postmenopausal women and men•Perimenopause causes a higher rate of increase in agalactosylated glycan structures•Perimenopause causes faster decrease of digalactosylated and monosialylated glycans•Proinflammatory IgG glycome may mediate the increased health risk in perimenopause Reproductive medicine; Molecular biology; Glycomics